The Response of Cow Urine Fertilizer and Rice Husk Charcoal to the Growth and Production of Sweet Mustard (Brassica Juncea L.) - Alfarizi Alfarizi; Desi Sri Pasca Sari Sembiring; Najla Lubis (Sean Institute, 2026)
This study aims to determine the response of cow urine liquid organic fertilizer (POC) and the use of rice husk charcoal on the growth and production of sweet mustard plants. This research method uses a Factorial Randomized Block Design (RAK) consisting of 2 factors with 48 plots, namely: The first factor is the provision of rice husk charcoal symbolized by